The Effect of Tetanus Toxoid Immunization Counseling on the Knowledge of Prospective Brides and Grooms at Wayabula Community Health Center - Fani Hirto; Widia Shofa Ilmiah (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Tetanus Toxoid (TT) immunization is a key preventive intervention to protect women of reproductive age and newborns from tetanus infection. Despite its importance, limited knowledge among prospective brides may reduce the effectiveness of TT immunization programs. This study aimed to analyze the effect of TT immunization counseling on the knowledge levels of prospective brides at Wayabula Public Health Center. A quantitative study using a quasi-experimental one-group pretest–posttest design was conducted involving 40 prospective brides selected through total sampling. Data were collected using a structured questionnaire measuring respondents’ knowledge before and after counseling. The Wilcoxon Signed Rank Test was used to analyze differences in knowledge levels. The results showed a significant improvement in knowledge after counseling, with the majority of respondents demonstrating higher posttest scores compared to pretest scores and no respondents experiencing a decrease in knowledge. These findings indicate that counseling plays an important role in enhancing understanding of TT immunization, including its purpose, benefits, and preventive value. In conclusion, TT immunization counseling is effective in improving knowledge among prospective brides and should be integrated as a mandatory component of routine immunization services. Strengthening counseling activities is expected to support informed decision-making, promote positive health behavior, and contribute to the prevention of tetanus in mothers and newborns.